Swine brucellosis in the state of Maranhão: Prevalence in slaughterhouses without sanitary inspection service - Lustosa Cavalcante, Analy (Pubvet, 2022)
Raising subsistence pigs is common in the state of Maranhão. Most of the time, this creation is mixed with cattle, canines and birds, being represented by loose animals, fed with leftovers of human food, with precarious slaughter, without sanitary inspection, exposed to the risk of contamination with pathogenic agents. Among the diseases that can affect the swine herd, brucellosis, an infectious disease caused by bacteria of the genus Brucella, which produces chronic infection in animals, can also infect humans, one of the most important and widespread zoonoses worldwide. Given this scenario, the objective of the study was to estimate the prevalence of anti-Brucella spp. in pigs slaughtered in slaughterhouses without inspection service. 224 swine serum samples were evaluated by the Buffered Acidified Antigen (AAT) screening test and confirmed by means of 2-Mercaptoethanol (2-ME) combined with Slow Seroagglutination (SAL). In the AAT test, 30/224 (13.39%) samples presented agglutination reaction in a total of 9/12 (75%) municipalities. In the 2-ME test, 3/224 (1.34%) samples were considered inconclusive and 12/224 (5.36%) positive samples in a total of 6/12 (50%) municipalities. These results demonstrate the presence of Brucella spp. in the swine species in the state of Maranhão which, in addition to being an imminent risk to public health, could harm the main objective of the National Program for the Control and Eradication of Brucellosis and Tuberculosis in cattle and buffaloes: the eradication of the disease.